A comparative study of maternal & neonatal outcome and patient satisfaction with intravaginal misoprostol versus intravenous oxytocin in patients with premature rupture of membranes beyond 36 weeks gestation - Shah, Bhaumik; Nagar, Noopur; Nagar, Shashwat S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Premature rupture of membranes (PROM) occurs in about 10% of patients beyond 36 weeks of gestation. In this situation, labor induction with prostaglandins, has been proved to be beneficial and results in decreased chorioamnionitis, neonatal antibiotic therapy, neonatal intensive care (NICU) admission, and increased maternal satisfaction. Many techniques for induction of labor are available. This prospective randomized comparative study was thus taken up to compare the outcomes of misoprostol versus oxytocin with respect to the maternal and neonatal outcomes and patient satisfaction. Methods: A prospective randomized study was carried out where 200 women admitted to department of obstetrics & gynecology, Pravara Rural Hospital, PMT, Loni with PROM beyond 36 weeks of gestation were included where 100 each were included in two groups- vaginal misoprostol group & oxytocin infusion group. Results: Nearly 58% of the cases of PROM were in the age group 21-25 yrs. Vaginal deliveries were 42% in misoprostol group, where as 44% in oxytocin group; whereas LSCS were 7% in misoprostol group and 5% in oxytocin group. Maximum number of cases had APGAR score between 7-10 in both the groups. Patients with misoprostol induction were more satisfied as compared to patients with oxytocin induction. Conclusions: Labor induction with oxytocin infusion for PROM beyond 36 weeks in an unfavorable cervix is associated with longer duration of the second stage and a higher risk of cesarean delivery for failure to progress in comparison to those with transvaginal misoprostol. Patients with misoprostol induction were more satisfied as compared to patients with oxytocin induction.